Taraf Hidup Keluarga Nelayan Soma Pajeko di Desa Likupang Kampung Ambong Kecamatan Likupang Timur Kabupaten Minahasa Utara - Makadada, Gabriela E.A.; Tambani, Grace O.; Durand, Swenekhe S.; Pangemanan, Jeannette F.; Andaki, Jardie A.; Kotambunan, Olvie V. (Universitas Sam Ratulangi, 2024)
Abstract The purpose of this study was to determine the amount and source of income of ABK Soma Pajeko families, and to determine the amount and type of family expenditure, and to determine the standard of living of ABK Soma Pajeko families in Likupang Village, Ambong Village. The method used in this study is the survey method. The population in this study were ABK Soma Pajeko who were married in Likupang Village, Ambong Village, totaling 11 people. The data collection method used the purposive purposive sampling method, the purposive sampling technique was used because of certain considerations. The data collected were primary data and secondary data. Primary data collection was carried out by means of interviews guided by questionnaires and observations. Secondary data collection was by citing existing data from related agencies or previous research. Data analysis used in this study was qualitative and quantitative descriptive analysis. The purpose of this study was achieved by analyzing household income calculations, analyzing ABK household expenditures and standard of living analyzed using the Engel Index. Based on the research results, it can be concluded that the average income of ABK Soma Pajeko families in Likupang Village, Ambongang Village is IDR 29,205,454 per year, sourced from their main job as ABK Soma Pajeko and side jobs. ABK Soma Pajeko family expenditure consists of total food expenditure plus total non-food expenditure. Food expenditure is IDR 16,512,272, and non-food expenditure is IDR 12,693,182, so that the total family expenditure is IDR 29,205,454 per year. The Engel Index analysis obtained was 56.5%, which means that 56.5% of the total income of ABK Soma Pajeko families in Likupang Village, Ambongang Village is used to meet food needs only. This means that the level of welfare of ABK Soma Pajeko in Likupang Village, Ambongang Village is still relatively low. Keywords: Standard of Living, ABK, Likupang Village, Ambong Abstrak Tujuan penelitian ini adalah untuk mengetahui jumlah dan sumber pendapatan keluarga ABK Soma Pajeko, dan untuk mengetahui jumlah dan jenis pengeluaran keluarga, serta untuk mengetahui taraf hidup keluarga ABK Soma Pajeko di Desa Likupang Kampung Ambong. Metode yang digunakan dalam penelitian ini yaitu metode survei. Populasi dalam penelitian ini ialah ABK Soma Pajeko yang sudah berkeluarga yang ada di Desa Likupang Kampung Ambong yang berjumlah 11 orang. Metode pengambilan data menggunakan metode purposive purposive sampling, teknik purposive sampling digunakan karena adanya pertimbangan tertentu. Data yang dikumpulkan yaitu data primer dan data sekunder. Pengumpulan data primer dilakukan dengan cara wawancara yang dipandu dengan kuisioner dan observasi. Pengumpulan data sekunder yaitu dengan mengutip data yang sudah ada dari instansi terkait ataupun penelitian yang terdahulu. Analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif kualitatif dan kuantitatif. Tujuan penelitian ini dicapai dengan analisis perhitungan pendapatan rumah tangga, analisis pengeluaran rumah tangga ABK dan taraf hidup di analisis dengan Indeks Engel. Berdasarkan hasil penelitian dapat disimpulkan bahwa rata-rata pendapatan keluarga ABK Soma Pajeko di Desa Likupang Kampung Ambongang adalah Rp. 29.205.454 per tahun, bersumber dari pekerjaan pokok sebagai ABK Soma Pajeko dan pekerjaan sampingan. Pengeluaran keluarga ABK Soma Pajeko terdiri dari total pengeluaran pangan ditambah total pengeluaran non pangan. Pengeluaran pangan sebesar Rp. 16.512.272, dan pengeluaran non pangan sebesar Rp. 12.693.182, sehingga total pengeluaran keluarga sebesar Rp. 29.205.454 per tahun. Analisis Indeks Engel yang diperoleh sebesar 56,5%, ini berarti bahwa 56,5% dari total pendapatan keluarga ABK Soma Pajeko di Desa Likupang Kampung Ambongang digunakan untuk memenuhi kebutuhan pangan saja. Hal ini berarti bahwa tingkat kesejahteraan ABK Soma Pajeko di Desa Likupang Kampung Ambongang masih tergolong rendah. Kata kunci: Taraf Hidup, ABK, Likupang Kampung Ambong